Legal Protection for Debtors When There Is a Transfer Of Debt By Creditors Without The Debtor's Consent - Jeremia Rizky Sianipar; Endang Prasetyawati (International Journal of Social Sciences and Humanities, 2024)
The legal protection extended to debtors when faced with creditor-initiated debt transfers conducted without their consent. In today's intricate financial milieu, such transfers wield substantial influence over debtor rights and obligations. The primary objective of this research is to scrutinize the existing legal frameworks designed to safeguard the interests of debtors in these scenarios. This examination encompasses an exploration of statutory provisions as well as pertinent judicial precedents that serve as cornerstones in fortifying debtor rights. Through a comparative lens, this study seeks to illuminate the diverse approaches adopted across jurisdictions in addressing concerns related to debtor protection. By evaluating the implications of non-consensual debt transfers, this research aims to deepen comprehension of the underlying issues and challenges encountered by debtors in asserting their rights in such circumstances. Moreover, this study considers the broader socio-economic ramifications of inadequate debtor protection, emphasizing the significance of procedural fairness and equitable debt relations in fostering confidence and stability in financial transactions. Ultimately, this paper endeavors to contribute to the ongoing discourse surrounding debtor protection within the realm of financial law, advocating for the enhancement of legal mechanisms to ensure the fair treatment of debtors and the preservation of their rights amidst evolving financial landscapes.